علاقة المنطق بالرياضيات عند رسل ـ " حساب الفئات " نموذجاً ـ - صالح, رشيد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
قام هذا البحث باستجلاء العلاقة بين المنطق المعاصر والرياضيات عند رسل، ولا سيما علاقة الرياضيات بـ " منطق الفئات "، لكي يبين أن الأفكار المنطقية والطرق الرياضية التي قدمها منطق رسل كان لها دورا كبيرا في اندماج المنطق بالرياضيات وانفصاله عن الفلسفة والنقاشات الميتافيزيقية. كما ناقش وفند الاعتقاد القائل بأن المنطق علم معياري له غايات فلسفية، من خلال التأكيد على أن المنطق المعاصر أصبح علما صوريا مستقلا يتمثل الطرق الهندسية والرياضية بشكل كامل. This research wants to understand the links between mathematics and modern logic according to Russel,s opinion, to explain that logical ideas and mathematical methods which are presented by Russel that played an important role that led to a combination between logic and mathematics. At the same time logic was separated from metaphysical discussions and philosophy. The research tries to falsify the opinion which says that logic is a science of criterions, and it has philosophical purposes through affirming that modern logic is an independent formal science, and this science uses completely mathematical and geometrical methods.